Morfofisiología y patología en el sistema reproductivo de la yegua: un enfoque microscópico (2021)
The objective of this work was to carry out a bibliographic review on the equine female reproductive system, approaching its anatomy, physiology and alterations with a microscopic approach. For this purpose, Google Scholar and Pubmed were used to search scientific articles, books and recognized web pages in Spanish and English. The endocrine control of the equine female's reproductive cycle is linked to the hypothalamus-pituitary-gonads axis, but the most important feature in this cycle is the photoperiod, which is carried out by the hormone melatonin. The estrous cycle is divided into estrus and diestrous, where estrus is the period when the mare is sexually receptive and her reproductive tract is ready to transport and receive sperm. The diestrous is the remaining part of the cycle, where there are no alterations in the animal's behavior. In mares, infectious alterations can be found such as: vaginitis, cervicitis, metritis, endometritis, among others; having different causes. The reproductive tract of the mare is a very complex and important subject, for this reason it is necessary to know it, since with good information about it, mainly in a histological approach, it will be possible to establish really effective treatments in the animals, there will be less economic and animal losses in this area and on the contrary, there will be favorable results and profits in a shorter time.